Patent citation: A technique for measuring the knowledge flow of information and innovation. (December 2017) - Sharma, P.; Tripathi, R.C.
Abstract: Knowledge cannot be bound, restricted or categorized. Knowledge is precisely an intangible strength that has a definite economic importance if well utilized and commercialized. Knowledge spillover is an occurrence, which is imaginable but difficult to have an effective measurement of it. Patents citation is a developing concept and has gained momentum in recent past. Patents citation contains valuable data and if analyzed well, may sometimes reveal concealed mysteries of the information flow between countries, laboratories, companies, and universities. Profuse technical research has been conducted on this topic by many scientists. Through these experiments, scientists have tried to show that the innovative information hidden in patents crosses every barrier and is taken by the research labs for its further expansion. Patents citation reveals the diffusion of information and its applicability into many other technical fields which give birth to a new technology. This paper presents a comprehensive survey of patents citation analysis covering and promoting the landmark research done in the field of patents citation, informing readers to consider this important segment of patent document as a field for analysis. Also, this paper presents an innovative methodology for generating patent citation network with the help of techniques of Information Retrievals.